Characterization of Amino Acid Mutations of Newcastle Disease Virus (NDV) In Swan Geese (Anser cygnoides) In East Java, Indonesia - Naimah Putri; Ine Karni (Journal of Applied Veterinary Science and Technology)
Background: Newcastle disease (ND) is a highly contagious viral disease affecting the poultry industry. The NDV is classified into three strains based on their relative virulence, namely velogenic or highly virulent, mesogenic or moderately virulent, and lentogenic or lowly virulent. The clinical manifestations of the disease vary depending on many factors, such as host susceptibility and the virulence of the NDV strain. Objective: This study aims to analyze the amino acid mutations of the NDV in unvaccinated swan goose (Anser cygnoides) from various locations in Java. Methods: Samples were collected through cloacal swabs and isolated by inoculation in Specific Pathogen-Free (SPF) embryonated eggs that were nine days old. Hemagglutination and hemagglutination inhibition tests were conducted to confirm that the isolated virus was NDV. The isolated virus was processed using reverse transcription-polymerase chain reaction (RT-PCR) with primers that amplified partial sequences of the fusion (F) gene, which was analyzed to determine the pathotype. Results: The results indicated the presence of mutations in several regions. The amino acid changes occurred in 17 variable sites (7.2%) between RefSeq/JF950510 and ND/SW1/2018, 12 variable sites (5.1%) between RefSeq/JF950510 and ND/SW2/2018, 13 variable sites (5.5%) between RefSeq/JF950510 and ND/SW3/2018, and 19 variable sites (8.1%) between RefSeq/JF950510 and ND/SW4/2018. The amino acid sequences of the cleavage site of the fusion (F) protein revealed that all isolates had low virulence. Conclusion: The results indicated that mutations in the region outside the cleavage site not were incapable of altering the virulence of the virus.